2006
DOI: 10.1039/b509868h
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyl functionalization of ultrasmall luminescent silicon nanoparticles through thermal hydrosilylation

Abstract: Functionalization of ultrasmall semiconductor nanoparticles to develop new luminescent probes that are optically bright, stable in aqueous environments, and sized comparably to small organic fluorophores would be of considerable utility for myriad applications in biology. Here, we report one of the first examples of thermal hydrosilylation between a bi-functional alkene and ultrasmall (y1 nm) H-passivated silicon nanoparticles (Si-np-H) to prepare strongly luminescent, water stable, carboxyl functionalized nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0
10

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(91 citation statements)
references
References 66 publications
6
75
0
10
Order By: Relevance
“…This modification preserves the strong PL of the Si core, adds a hydrophilic interface for stability in aqueous media, and is easily reacted with primary amines to label biomolecules, all while adding only a small amount to the overall size. 7 Work with the Si and Ge systems has also shown that surface chemistry can play a more direct role in their photophysical behavior. The analysis has generally focused on the source of PL and the debate between the quantum confinement (delocalized) and surface state (localized) mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…This modification preserves the strong PL of the Si core, adds a hydrophilic interface for stability in aqueous media, and is easily reacted with primary amines to label biomolecules, all while adding only a small amount to the overall size. 7 Work with the Si and Ge systems has also shown that surface chemistry can play a more direct role in their photophysical behavior. The analysis has generally focused on the source of PL and the debate between the quantum confinement (delocalized) and surface state (localized) mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…10 The Si-np-COOH were shown to preserve the strong fluorescence of the Si core, have sizes comparable to small organic fluorophores ͑ϳ1 nm͒, and to be stable in polar solutions. The carboxyl functionality can also be reacted with primary amines to attach them to various biomolecules.…”
mentioning
confidence: 99%
“…As can be seen in Figure 2.1, the IR spectrum of the dried polymer contains overlapping peaks at 1050 cm -1 and 1090 cm -1 , both of which are in the region that has been attributed to Si-O bonding. 9,34,40,47,58,63,69,72,[75][76][77][78][79][80][81][82][83] Evidence for the preservation of Si-H bonding is also shown by the peak at 2240 cm -1 in the IR spectrum.…”
Section: Synthesis Of Polymeric Hsio 15 From Hsiclmentioning
confidence: 91%
“…[36][37][38][39] In addition, Si NPs have been envisioned as replacements for traditional organic dyes in a variety of sensing and tracking applications owing to their strong visible PL and superior resistance to photobleaching and photodegredation. 22,23,[40][41][42] For biomedical imaging and sensing applications, red-to-NIR-fluorescence is desired, since these wavelengths penetrate tissue, and do not damage cells. While the number of red-to-NIR-emitting molecular organic dyes is limited (e.g., to…”
Section: Technological Developments Leading To Photoluminescent Siliconmentioning
confidence: 99%
See 1 more Smart Citation